Evaluation of different spatial techniques to analyze the occurrence of dengue in Rio Claro - SP. - Domingues, Jacqueline [UNESP]; Govone, José Sílvio [UNESP] (Revista Brasileira de Biometria, 2019)
In this paper we have developed a study of dengue fever in Rio Claro, Sao Paulo - Brazil. The Municipal Health Foundation of Rio Claro provided data about reported cases of dengue fever in 2011. The main objective was to analyze both the spatial distribution of the disease in the city, by Census tracts, and the relationship of the disease with socioeconomic factors. Two types of spatial models were applied to the data: the SAR model Simultaneous Autoregressive Models and SEM - Simultaneous Error Models. We also fitted the classic linear model, just for comparison to the two spatial models. The results showed that dengue is related to socioeconomic factors and, through the models it was possible to identify which one was statistically significant. Thematic maps have identified the areas that have the highest concentration of the disease.
Avaliação de diferentes técnicas espaciais para análise da ocorrência de dengue em Rio Claro-SP
Keywords: Dengue; Epidemiology; Simultaneous autoregressive models (SAR); Simultaneous error models (SEM); Spatial analisys